2021
DOI: 10.3389/fbioe.2021.719047
|View full text |Cite
|
Sign up to set email alerts
|

Reparative and Maladaptive Inflammation in Tendon Healing

Abstract: Tendon injuries are common and debilitating, with non-regenerative healing often resulting in chronic disease. While there has been considerable progress in identifying the cellular and molecular regulators of tendon healing, the role of inflammation in tendon healing is less well understood. While inflammation underlies chronic tendinopathy, it also aids debris clearance and signals tissue repair. Here, we highlight recent findings in this area, focusing on the cells and cytokines involved in reparative infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 189 publications
(259 reference statements)
1
51
0
Order By: Relevance
“…Recent works have proved that tenocytes participate in the amplification of the inflammatory response after tendon damage through the secretion of different cytokines and chemokines [ 66 ]. On the other hand, IL-4 promotes the transformation of naive CD4 T cells and macrophages into a Th2 T cell or M2 macrophage phenotype, respectively, which drives the type 2 anti-inflammatory immune response [ 67 ]. Thus, it is plausible that tenocytes can also have a role in the modulation of the reparative (anti-inflammatory) immune response, which should be studied in future works.…”
Section: Resultsmentioning
confidence: 99%
“…Recent works have proved that tenocytes participate in the amplification of the inflammatory response after tendon damage through the secretion of different cytokines and chemokines [ 66 ]. On the other hand, IL-4 promotes the transformation of naive CD4 T cells and macrophages into a Th2 T cell or M2 macrophage phenotype, respectively, which drives the type 2 anti-inflammatory immune response [ 67 ]. Thus, it is plausible that tenocytes can also have a role in the modulation of the reparative (anti-inflammatory) immune response, which should be studied in future works.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, as research in tendinopathy pathophysiology has firmly identified a chronic degeneration of the matrix microenvironment, it is now increasingly evident that inflammatory responses are continuously activated within the tendon matrix microenvironment during tissue injury and contribute to dysregulated homeostasis ( Millar et al, 2017 ). However, advancements in cellular profiling using genetic and molecular tools enabled research demonstrating the presence of mast cells, granulocytes, macrophages, T cells, and B cells in both acute and chronic human tendinopathic tissues ( Arvind and Huang 2021 ). In this study, we identified p-sites of proteins involved in neutrophil reaction that were upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…The recruited cells start to secrete pro-inflammatory cytokines and chemokines, hence increasing the immune cell recruitment and promoting inflammation ( Figure 3 C) [ 32 ]. Afterwards, immune cells from the adaptive immune response including B cells, CD4+ and CD8+ T cells, natural killer (NK) cells, and innate lymphoid cells start to release cytokines and chemokines within the implanted site [ 32 , 79 , 80 , 81 ]. The occurrence of acute and chronic inflammation is followed by the formation of neovascularized connective tissue, called granulation tissue.…”
Section: Immune Response Induced By Scaffold Implantationmentioning
confidence: 99%